Penguatan Strategi Pemasaran Rawat Jalan Eksekutif Rumah Sakit Melalui Penyelenggaraan Webinar DCG Indonesia di LMS Plataransehat Kemenkes - Anandito Birowo; Tri Lestari (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
The increasingly competitive health care industry requires hospitals to strengthen executive outpatient services through targeted marketing strategies and capacity building. As a training institution accredited by the Ministry of Health, DCG Indonesia organized a free webinar entitled “Marketing Strategies for Executive Outpatient Services in Hospitals” to fulfill accreditation requirements and support continuing education. This article describes the planning, implementation, and outcomes of the two-hour webinar, which used lectures, discussions, and question–answer sessions and was integrated with the Plataransehat LMS for pre-test, post-test, and evaluation. Of 60 targeted participants, 29 (48%) completed the full learning sequence. The mean knowledge score increased from 60.69 to 75.17 (a gain of about 24%), while overall participant satisfaction reached 93.76%, with very good ratings for instructors, materials, and event management. The webinar was effective in enhancing knowledge and providing practical guidance for hospitals in designing comprehensive, context-sensitive, and evidence-based marketing strategies for executive outpatient services.